Solve for g 2y-6g=6

Math
2y-6g=6
Subtract 2y from both sides of the equation.
-6g=6-2y
Divide each term by -6 and simplify.
Tap for more steps…
Divide each term in -6g=6-2y by -6.
-6g-6=6-6+-2y-6
Cancel the common factor of -6.
Tap for more steps…
Cancel the common factor.
-6g-6=6-6+-2y-6
Divide g by 1.
g=6-6+-2y-6
g=6-6+-2y-6
Simplify each term.
Tap for more steps…
Divide 6 by -6.
g=-1+-2y-6
Cancel the common factor of -2 and -6.
Tap for more steps…
Factor -2 out of -2y.
g=-1+-2(y)-6
Cancel the common factors.
Tap for more steps…
Factor -2 out of -6.
g=-1+-2(y)-2(3)
Cancel the common factor.
g=-1+-2y-2⋅3
Rewrite the expression.
g=-1+y3
g=-1+y3
g=-1+y3
g=-1+y3
g=-1+y3
Solve for g 2y-6g=6

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top